2014
DOI: 10.3758/s13421-014-0428-8
|View full text |Cite
|
Sign up to set email alerts
|

The roles of associative and executive processes in creative cognition

Abstract: How does the mind produce creative ideas? Past research has pointed to important roles of both executive and associative processes in creative cognition. But such work has largely focused on the influence of one ability or the other-executive or associative-so the extent to which both abilities may jointly affect creative thought remains unclear. Using multivariate structural equation modeling, we conducted two studies to determine the relative influences of executive and associative processes in domain-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
322
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 379 publications
(364 citation statements)
references
References 63 publications
30
322
1
11
Order By: Relevance
“…observation is consistent with prior research on the "path of least resistance" in creative production (Ward, 1994), and other work that has shown that instructions to "be creative" can yield substantial improvements to creative output : People generally need to expend cognitive effort to overcome initial biases toward less creative responses (e.g., using cognitive control to inhibit more accessible but less creative responses; Beaty, Silvia, Nusbaum, Jauk, & Benedek, 2014). In light of this, it may be useful to think of these results as describing the effects of room size on "default" problem solving (i.e., when participants are not necessarily actively trying to be creative in their responses).…”
Section: Figuresupporting
confidence: 73%
“…observation is consistent with prior research on the "path of least resistance" in creative production (Ward, 1994), and other work that has shown that instructions to "be creative" can yield substantial improvements to creative output : People generally need to expend cognitive effort to overcome initial biases toward less creative responses (e.g., using cognitive control to inhibit more accessible but less creative responses; Beaty, Silvia, Nusbaum, Jauk, & Benedek, 2014). In light of this, it may be useful to think of these results as describing the effects of room size on "default" problem solving (i.e., when participants are not necessarily actively trying to be creative in their responses).…”
Section: Figuresupporting
confidence: 73%
“…The extent to which creative thought relies upon such top-down and bottomup processes remains a point of debate in the literature on musical improvisation as well as in the literature on domain-general creative cognition (cf. Abraham, 2014;Beaty et al, 2014c;Jung et al, 2013;McMillan et al, 2013;Mok, 2014;Sowden et al, 2014).…”
Section: Pressing's Model Of Improvisationmentioning
confidence: 98%
“…Since Mednick's seminal theory, other theories of creative cognition have emerged, and all suggest the structure of associative memory is critical for creative cognition (Beaty, Silvia, Nusbaum, Jauk, & Benedek, 2014;Gabora, in press;Sowden, world networks-act as "shortcuts" to access remote associations and facilitate the flexible search through possible solutions.…”
Section: Divergent Thinking Divergent Thinking (Dt) Is a Common Proxmentioning
confidence: 99%